2014
DOI: 10.1517/13543784.2015.960077
|View full text |Cite
|
Sign up to set email alerts
|

Investigational cancer drugs targeting cell metabolism in clinical development

Abstract: Introduction Malignant cell transformation and tumor progression are associated with alterations in glycolysis, fatty acid synthesis, amino acid delivery and production of reactive oxygen species. With increased understanding of the role of metabolism in tumors, there has been interest in developing agents that target tumor specific metabolic pathways. Numerous promising agents targeting altered metabolic pathways are currently in Phase I – III clinical trials. Areas covered This paper reviews the early phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 100 publications
1
44
0
1
Order By: Relevance
“…One such HK inhibitors in the clinic is Lonidamine (TH-070), a derivative of indazole-3-carboxylic acid. A Phase II trial in 35 patients with ovarian cancer showed an 80% objective response rate (ORR) of TH-070 in combination with paclitaxel and cisplatin (35). A Phase II trial in 31 patients with NSCLC who were treated with TH-070 in combination with cisplatin, epidoxorubicin and vindesine showed 89% of patients had either a partial remission (PR) or stable disease (SD) (35).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
See 4 more Smart Citations
“…One such HK inhibitors in the clinic is Lonidamine (TH-070), a derivative of indazole-3-carboxylic acid. A Phase II trial in 35 patients with ovarian cancer showed an 80% objective response rate (ORR) of TH-070 in combination with paclitaxel and cisplatin (35). A Phase II trial in 31 patients with NSCLC who were treated with TH-070 in combination with cisplatin, epidoxorubicin and vindesine showed 89% of patients had either a partial remission (PR) or stable disease (SD) (35).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…A Phase II trial in 35 patients with ovarian cancer showed an 80% objective response rate (ORR) of TH-070 in combination with paclitaxel and cisplatin (35). A Phase II trial in 31 patients with NSCLC who were treated with TH-070 in combination with cisplatin, epidoxorubicin and vindesine showed 89% of patients had either a partial remission (PR) or stable disease (SD) (35). Despite this early promising trials, TH-070 development was terminated after disappointing results in two randomized Phase III trials (35).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
See 3 more Smart Citations